An Overview of Generation Z's Mental Health - Popa, Brigitte (New Trends in Psychology, 2024)
The mental health of Generation Z, born between 1997 and 2012, has become a central concern in modern psychology. This age group is facing a multitude of risk factors that impact their psychological well-being. This article provides an overview of the primary mental health disorders affecting today's youth, including anxiety, depression, and Attention Deficit Hyperactivity Disorder (ADHD). The exploration of these conditions is grounded in an understanding of the unique external and internal pressures faced by Generation Z, such as economic uncertainty, rapid social changes, and educational challenges. The objective of this paper is to elucidate how these three mental health disorders impact both daily functioning and the personal and professional development of young people, as well as to identify effective resources and support strategies to reduce symptomatology and promote resilience. Furthermore, the importance of mental health education and early intervention is highlighted, as these play a crucial role in preventing the chronicity of these conditions and supporting a generation capable of reaching its full potential.